FACTOR ANALYSIS OF THE PHENOMENON OF MASS LAYOFFS AT STARTUPS: MIXED METHOD APPROACH WITH STRUCTURAL EQUATION MODELING - Wahyu Fahrul Ridho; Nurul Azizah (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
Massive layoffs have occurred amid the rapid growth of startup companies in recent years. This study aims to explore the factors that play a role in the phenomenon of massive startup layoffs. This research use mixed method approach because it is still early to understand the problem. Structured approach is used to construct phenomena through secondary data. From the research results on these variables, results and conclusions are drawn that the phenomenon of startup layoffs is multifactor. The business model that relies on venture capital funding, the priority of growth at the expense of cash flow, and the high cost of startup employees are factors that trigger startups to adopt a mass layoff strategy when macroeconomic factors make venture capital reduce funding and make market conditions unfavourable to grow. While from statistical analysis using PLS-SEM show that funding and startup industry have significant effect on the number of layoff. This research can be a starting point for describing the phenomenon of mass startup layoffs, but it is only limited to exploratory studies related to variables that contribute to the phenomenon. Further research is needed to delve deeper into other factors that make startups more vulnerable to adopting layoff strategies.